Isolation and Molecular Identification of Indole Acetic Acid-Producing Endophytic Bacteria from Daun Dewa Plant (Gynura divaricata (L.) DC) - Ratna Dewi Setyowati; Artini Pangastuti; Ari Susilowati (Universitas Muhammadiyah Surakarta, 2023)
Indole acetic acid (IAA) is an auxin hormone that can regulate plant growth and development. Bacteria produce IAA through L-tryptophan metabolism. The purpose of this study was to determine the ability of endophytic bacteria isolated from Daun Dewa plants to produce IAA to increase the germination and growth of tomato seedlings. Isolation of endophytic bacteria was carried out by sterilizing plant surfaces. The production of IAA is done by adding L-tryptophan precursors. The results showed that there were six endophytic bacteria, and three isolates of them have the potential to produce IAA, namely: AD1.1, UD1.1, and UD2.1. The highest IAA concentration was produced by isolate AD1.1. Growth in sprouts is significantly influenced by the concentration of IAA; the higher the concentration of IAA, the longer the shoots and the roots. Based on the 16S rRNA gene sequence, these isolates belong to the genus Klebsiella.